2012
DOI: 10.1164/rccm.201107-1199ci
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and Processing of Endobronchial Ultrasound-guided Transbronchial Needle Aspiration Specimens in the Era of Targeted Lung Cancer Chemotherapy

Abstract: Recent advances in therapy for non-small cell lung carcinoma have shown that a personalized approach to treatment has the potential to significantly reduce lung cancer mortality. Concurrently, endoscopic ultrasound transbronchial needle aspiration has emerged as an accurate and sensitive tool for the diagnosis and staging of this disease. As knowledge of the molecular mechanisms that drive lung cancer progression increases, the amount of information that must be derived from a tumor specimen will also increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 61 publications
0
39
0
1
Order By: Relevance
“…In certain countries and settings, they provide medical treatment for the cancer (e.g., chemotherapy and biologics), endobronchial treatment (e.g., brachytherapy), general supportive care, and terminal care. (2). These targeted therapies are a promising new approach that requires meticulous attention by pulmonologists to provide adequate tissue sampling through the competent use of endoscopic procedures.…”
Section: Executive Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…In certain countries and settings, they provide medical treatment for the cancer (e.g., chemotherapy and biologics), endobronchial treatment (e.g., brachytherapy), general supportive care, and terminal care. (2). These targeted therapies are a promising new approach that requires meticulous attention by pulmonologists to provide adequate tissue sampling through the competent use of endoscopic procedures.…”
Section: Executive Summarymentioning
confidence: 99%
“…Potentially all treatment decisions, at the time of diagnosis and later, will be based on the information obtained from that specimen. Therefore, it is essential that the specimen collection and processing procedures be optimized to ensure that the quality and quantity of the specimen are adequate to provide answers to all the questions that may be asked (2).…”
Section: Early and Specific Diagnosismentioning
confidence: 99%
“…26 These fi ndings have prompted a major shift toward targeted therapy in lung cancer management, as detailed by Socinski et al 27 in the article, "Treatment of Stage IV Non-small Cell Lung Cancer," in the American College of Chest Physicians Lung Cancer Guidelines, thus mandating that diagnostic specimens be acquired and processed in a fashion that permits the histologic subtyping of NSCLC. 28 In studies using immunostains to subtype NSCLC in cytologic specimens, Loo et al 29 and Nicholson et al 30 showed that thyroid transcription factor-1 and mucin vs p63 stains are the best stains for detecting adenocarcinoma vs SCC, respectively . However, none of the antibodies used in immunohistochemistry is 100% specifi c and sensitive for this differential diagnosis.…”
Section: Lung Carcinogenesismentioning
confidence: 99%
“…Presently, lung cancer treatment is based on the histologic subtyping of NSCLC (13,14). Our study strongly suggests that ENB is an outstanding technique that can aid pulmonary physicians in small lung lesions diagnosis.…”
Section: Discussionmentioning
confidence: 71%